Peran Teknologi dalam Pembelajaran Pendidikan Agama Islam - Oga Sugianto; Lailatul Munawaroh; Indah Supriani; Heri Nur Cahyono; Nyairoh Nyairoh (Civiliza Publishing, 2023)
This study aims to determine the role of technology in learning Islamic Religious Education, which in school institutions often results in failure, even though these students have been given these lessons, they often do not use them and do not apply what they have learned through their schools. This type of research is qualitative research using the Libery Research Method. Because this research is descriptive and uses analysis. Technology in PAI learning helps students understand the material taught by teachers, such as using the internet to communicate with teachers and students, using meeting room applications to create internet-based classrooms, and using audio and visual media. The constructivist paradigm of learning Islamic religious education argues that for PAI learning to be meaningful, students must be actively involved in acquiring knowledge about it. This is expected to have an impact on the formation of students' desire to practice worship and muamalah as a result of Islamic religious education